S100 chemokines mediate bookmarking of premetastatic niches - Rafii, Shahin (2006)
Primary tumours release soluble factors, including VEGF-A, TGFβ and TNFα, which induce expression of the chemokines S100A8 and S100A9 in the myeloid and endothelial cells within the lung before tumour metastasis. These chemokine-activated premetastatic niches support adhesion and invasion of disseminating malignant cells, thereby establishing a fertile habitat for metastatic tumours.